2013
DOI: 10.1177/1477153513512459
|View full text |Cite
|
Sign up to set email alerts
|

Correspondence: Comparing LED luminaires

Abstract: A recent editorial in Lighting Research and Technology 1 suggested the need for 'a simple set of questions to ask the LED supplier'. This letter presents such a set of questions, but also, and perhaps more importantly, a set of responses that might be considered appropriate. The information used to form these questions and answers has been drawn from a number of useful resources, 2-7 interaction with various lighting professionals and through the author's own experience. The purpose of these questions is to ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Boyce [12] challenged the lighting community to address this and suggested that a valuable contribution would be a set of standard, simple questions to ask the LED supplier. Duff [23][24][25][26] has provided Boyce with a set of these questions and appropriate answers in the LR&T (Lighting Research and Technology) and SDAR (Journal of Sustainable Engineering Design).…”
Section: Light Emitting Diodesmentioning
confidence: 99%
“…Boyce [12] challenged the lighting community to address this and suggested that a valuable contribution would be a set of standard, simple questions to ask the LED supplier. Duff [23][24][25][26] has provided Boyce with a set of these questions and appropriate answers in the LR&T (Lighting Research and Technology) and SDAR (Journal of Sustainable Engineering Design).…”
Section: Light Emitting Diodesmentioning
confidence: 99%